"EDUCATION LAW" IN THE NEW EDITION IS A KEY FACTOR OF ADAPTING THE NATIONAL EDUCATION SYSTEM TO INTERNATIONAL STANDARDS (World Bulletin of Social Sciences, 2021)
The article examines the content and significance of the adopted regulatory documents on the implementation of the right to education, as well as entering the world educational space. The system of measures developed for integration into the world education system is analyzed. The content of the new edition of the Law "On Education" is also disclosed.
Keywords: The right to education; modern education; the world community; inclusion